Cross species amplification of ikan kelah, Tor tambroides by using Mystus nemurus microsatellite markers - Keong, Remmy Bun Poh; Siraj, Siti Shapor; Daud, Siti Khalijah (Universiti Putra Malaysia Press, 2008)
Thirty eight microsatellite markers developed from a Random Hybridising Microsatellite (RAMs) enrichment protocol created from the DNA of the river catfish, ikan baung, Mystus nemurus were screened to cross amplify ikan kelah, Tor tambroides . Only five primers which amplified bands at the expected allele size regions were used for characterizing this species. The observed heterozygosity values were higher than the expected heterozygosity values for the bands amplified by primer pairs MnSC4-3B, MnLR2-1-52A and MnRmC3-1 across the three populations but the bands amplified by primer pairs MnSC4-1A and MnLR2-1-17B showed lower observed heterozygosity values than the expected heterozygosity values. The mean FIS value across the three populations was negative, indicating no deficit in heterozygosity. The mean value of FST was low indicating no gene was fixed within populations relative to the total population. The high value of Nm suggested high gene flow among the three populations. Both the (x2) chi-square and the (G2) likelihood ratio tests showed significant differences (P<0.05), indicating deviations from Hardy-Weinberg equilibrium in most loci except for one locus (MnSC4-1A) in the Negeri Sembilan population and two loci (MnLR2-1-52A and MnSC4-1A) in the Kelantan population. The genetic distance values generated ranged from 0.1053 to 0.1960. The UPGMA dendrograms constructed from the genetic distances based on the microsatellite markers showed that the Negeri Sembilan and Kelantan populations shared a similar cluster while the Pahang population was on its own.